Hemochromatosis associated with Parkinson's Disease (Research, Society and Development, 2025)
Iron is an essential mineral found in all living organisms and plays a key role in numerous physiological processes, including growth, development, and various cellular functions. This study aims to review the literature on the association between iron metabolism, hemochromatosis, and Parkinson’s disease (PD), assessing how iron accumulation may negatively affect health and potentially contribute to the development or progression of PD. This is a qualitative literature review conducted in August 2024. The research was carried out using the Scopus and PubMed databases, resulting in the selection of 25 studies. The objective was to analyze the role of iron accumulation in PD, identifying patterns and gaps in current evidence. In the nervous system, iron plays a critical role in mitochondrial respiration, myelin formation, and neurotransmitter metabolism—functions essential for maintaining neuronal health and cognitive performance. However, excess iron can lead to the production of free radicals, causing oxidative damage that significantly contributes to the onset of various pathological conditions. Since the human body lacks widely efficient mechanisms to eliminate excess iron, the regulation of its absorption, transport, and storage is crucial to prevent toxicity and its harmful effects on the nervous system.